An innovative approach in physical education: Exploring the impact of interactive virtual reality on motor skills - Utamayasa, I Gede Dharma; Mardhika , Riga (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background Problems: Recent advancements in virtual reality (VR) technology have expanded its practical application in enhancing physical activity and motor skill acquisition among children. Research Objectives: This study aims to investigate the impact of interactive virtual reality software on the motor skills of 11- to 12-year-old elementary school children. Methods: Employing a quantitative approach with quasi-experimental methods, the research was conducted on 34 students from Lontar 481 Public Elementary School in Surabaya, selected through purposive sampling. The instruments used in the physical education learning process using virtual reality media include pre-test and post-test stages, which combine understanding of motor skills, practice, and evaluation by the teacher based on the correctness, fluency, and completeness of student actions. The procedure involved the treatment of experimental group subjects using virtual reality for 40 minutes in the control group, which was carried out conventionally. It was analysed using SPSS via a t-test, and the significance level was set at P < 0.05. Findings/Results: These findings showed a significant positive impact of virtual reality technology on students' motor development and confidence in performing movements, compared to the control group who underwent traditional learning. Conclusion: Research shows that utilising virtual reality programmes increases students' confidence in learning physical activities, especially for those at lower performance levels. The novelty of this research lies in its demonstration of virtual reality's capacity to improve children's motor competence in the context of physical education. Overall, the findings of this study contribute to physical activity and motor skills regarding the use of virtual reality media for elementary school children.